Quantitative three‐dimensional echocardiographic analysis of the bicuspid aortic valve and aortic root: A single modality approach. Issue 2 (3rd December 2019) - Levack, Melissa M.; Mecozzi, Gianclaudio; Jainandunsing, Jayant S.; Bouma, Wobbe; Jassar, Arminder S.; Pouch, Alison M.; Yushkevich, Paul A.; Mariani, Massimo A.; Jackson, Benjamin M.; Gorman, Joseph H.; Gorman, Robert C.
Abstract: Background: Patients with bicuspid aortic valves (BAV) are heterogeneous with regard to patterns of root remodeling and valvular dysfunction. Two‐dimensional echocardiography is the standard surveillance modality for patients with aortic valve dysfunction. However, ancillary computed tomography or magnetic resonance imaging is often necessary to characterize associated patterns of aortic root pathology. Conversely, the pairing of three‐dimensional (3D) echocardiography with novel quantitative modeling techniques allows for a single modality description of the entire root complex. We sought to determine 3D aortic valve and root geometry with this quantitative approach. Methods: Transesophageal real‐time 3D echocardiography was performed in five patients with tricuspid aortic valves (TAV) and in five patients with BAV. No patient had evidence of valvular dysfunction or aortic root pathology. A customized image analysis protocol was used to assess 3D aortic annular, valvular, and root geometry. Results: Annular, sinus and sinotubular junction diameters and areas were similar in both groups. Coaptation length and area were higher in the TAV group (7.25 ±  0.98 mm and 298 ± 118 mm 2, respectively) compared to the BAV group (5.67 ± 1.33 mm and 177 ± 43 mm 2 ; P  = .07 and P  = .01). Cusp surface area to annular area, coaptation height, and the sub‐ and supravalvular tenting indices did not differ significantly between groups. Conclusions: Single modality 3D echocardiography‐based modeling allows for a quantitative description of the aortic valve and root geometry. This technique together with novel indices will improve our understanding of normal and pathologic geometry in the BAV population and may help to identify geometric predictors of adverse remodeling and guide tailored surgical therapy.